Giant plexiform neurofibroma of the sciatic nerve in a Burkinabé adult - Gustavo Frómeta Díaz (Centro Provincial de Información de Ciencias Médicas, 2021)
The case report of a 36 years patient with pathological history of Von Reklinghausen disease is presented. She was assisted in the General Surgery Service of the Hospital Center from Kossodô in Burkina Faso presenting a giant tumor in the back region of the right thigh. The complementary exams confirmed the presumed diagnosis of giant plexiform neurofibroma of the sciatic nerve. During the surgical procedure an uncommon tumor was removed which weight exceeded the 22.5 kg. With the postoperative rehabilitative treatment of the operated member the patient had a favorable clinical course and she was discharged from the hospital 7 days later.